ANALISIS HUKUM ISLAM TERHADAP UNDIAN BERHADIAH UMRAH DALAM APLIKASI MUDA>RABAH DI BMT BINA INSAN MANDIRI CABANG LOGAWE KECAMATAN RENGEL KABUPATEN TUBAN - A. Jauhari Nashrullah (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2016)
This thesis is the result of field research (field research) in BMT Bina Insan Mandiri Branch Logawe. Data collection techniques used in this research is the method of observation and interview (interview). Furthermore, the data collected compiled and analyzed using descriptive analysis method, which collects data on Lottery Umrah in Mudarabah Application in BMT Bina Insan Mandiri Branch Logawe the District Rengel District Tuban whichÂ be accompanied with analysis to be concluded. In the study it can be concluded that, Mudarabah applications in products Si BerkahÂ (Simpanan Berangkat ke Mekah) in BMT Bina Insan Mandiri Branch Logawe the District Rengel District Tuban which ise Mudarabah contract, along with the results of BMT Bina Insan Mandiri done in accordance with the provisions of the initial contract product Si Berkah BMT Bina Insan Mandiri by usingÂ Mudarabah contract. with the percentage of profit sharing by 2% for customers and 98% for BMT Bina Insan Mandiri Branch Logawe the District Rengel District Tuban, this ratio could be taken advantage of each month or at the time of maturity. From the analysis the authors concluded that, lottery Umrah in mudarabah application at BMT Bina Insan Mandiri Branch Logawe the District Rengel District Tuban are aspects maslahah and harm the social and economic viewpoints society, lottery Umrah this be done, because there is a lack of certainty refund customers in full for two million dollars to customers who follow lottery Umrah and providing gifts Umrah is a third party that BMT Bina Insan Mandiri.